THE INTRICACY OF VIOLENCE AND PEACE IN MARI BY EASTERINE KIRE - Dr. R. Nimmi; Dr. V. David Arputha Raj (The Bioscan, 2025)
Literature has its own way of expressing the culture and the society its suffering and its abundance in natural wealth. Trauma is often considered as an emotional response to a terrible event like an accident, rape or natural disaster. It is often defined by the long term reactions. When a culture or a society in terms of experiencing traumatic events can be called as cultural trauma. The traumatising events interact with human nature and when the basic human needs of love, security, order and connection are destabilised for the people, they get traumatised. The novel Mari by Easterine Kire talks about the naked reality of the war that is fought in Kohima in particular and Nagaland in general. Though the Nagas were not directly associated with the war but the most affected were these people. They were victimised, marginalised and the people were used for the selfish purpose in the pre and the post war situation. Though they recover from the past events, the memory of the past bring them the suffering of the trauma.